2001
DOI: 10.1038/oby.2001.32
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Prevalence of Obesity in the Workers of a General Hospital in Mexico

Abstract: FANGHÄ NEL, GUILLERMO, LETICIA SÁ NCHEZ-REYES, ARTURO BERBER, AND ROSARIO GÓ MEZ-SANTOS. Evolution of the prevalence of obesity in the workers of a general hospital in Mexico. Obes Res. 2001;9: 268 -273. Objective: The objective of this study was to compare the prevalence of overweight and obesity in the first Prevalencia de factores de nesso cardiovascular en Trabajadores survey (1994) with the prevalence of overweight and obesity observed in the second survey (1996). Research Methods and Procedures: For bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
2
7
1
Order By: Relevance
“…This was not surprising and remains consistent with the most recent studies analyzing the performance of glucose meters (5,17,25,28).…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…This was not surprising and remains consistent with the most recent studies analyzing the performance of glucose meters (5,17,25,28).…”
Section: Methodssupporting
confidence: 76%
“…All the studies relating to accuracy and precision of home blood glucose meters were performed in a crosssectional manner (4,8,(15)(16)(17)(18). Our results suggest that the older glucose meters from the late 1980s have similar accuracy to the newer ones.…”
Section: Methodsmentioning
confidence: 69%
“…18,19 The included population may be consider as representative of middle class urban population in Mexico City; so the obtained results may not be readily applied to the rest of the Mexican population, for instance countryside populations, or populations from other regions of the country.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, for example, both adults (43)(44)(45) and children (17,44,45) are struggling with overweight. Investigators reported that the rates of overweight in young Mexican children (under 5 years old) are 19% (45).…”
mentioning
confidence: 99%